GAMBARAN TINDAKAN DIET SURVIVOR KANKER PAYUDARA DI LUAR DAN DI DALAM RUMAH SINGGAH YKI JAWA TIMUR - Meyrina Putri Cahyariani; Annis Catur Adi (Universitas Airlangga, 2016)
Dietary action is a dietary practice of cancer survivor by carefully chosing food types that consumed. It have an important role for cancer survivor in prevent breast cancer recurence. Efforts to prevent cancer also carried out byRumah Singgah Yayasan Kanker Indonesia Jawa Timur (YKI JATIM) which is one of the organizations or communities that have cancer awareness, accommodate and facilitate patients or cancer survivor who are battling cancer. Thepurpose of the study was to describe dietary action of breast cancer survivor in outside and inside Rumah Singgah YKI JATIM using theory of Health Belief Model framework. The study was an observational study with cross sectionaldesign and a qualitative approach. The sample was 4 participants inside and outside Rumah Singgah taken by snowball sampling and accidental sampling. Methods of data collection used was in-depth interviews, recorder and observation. The result showed that breast cancer survivor dietary practice among inside and outside Rumah Singgah YKI JATIM have the same tendency to practice a healthy dietary. Dietary participant among outside YKI JATIM are infl uenced by knowledge, level of education, and strong perception factor. Effort of healthy promotion about healthy diet for breast cancer survivor, families, and promotion at the community level need to be improved, which are expected to encourage breast cancer survivor to maintain their dietary action.Keywords: action of dietary, breast cancer survivor, Health Belief Model